2008
DOI: 10.1007/s11010-008-9755-z
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus induces an oxidative stress during the early stages of infection in B lymphocytes, epithelial, and lymphoblastoid cell lines

Abstract: The study investigates the direct effect of Epstein-Barr virus infection on the oxidative profile of in vitro cultivated human cells. For this purpose, a panel of human EBV target cells presenting heterogeneity in their cellular and culture types (epithelial cells or lymphocytes; primary culture or continuous cell culture) was selected. These cells are purified human B lymphocytes, DG75, 293, and HepG2 cell lines. The oxidative stress was evaluated during the early stages of infection (2, 12, and 24 h) by meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 37 publications
0
72
1
2
Order By: Relevance
“…These observations are consistent with those of Gruhne et al (20), who found that EBNA1 increased ROS and NOX2 levels in B cells. In addition, primary EBV infection has been shown to increase oxidative stress in B cells, epithelial cells, and lymphoblastoid cell lines (30), as well as in EBV-positive tumor cells (5,10). In contrast to our results, Gruhne et al (20) reported that EBNA1 did not affect ROS or NOX2 transcripts in epithelial cells.…”
Section: Discussioncontrasting
confidence: 99%
“…These observations are consistent with those of Gruhne et al (20), who found that EBNA1 increased ROS and NOX2 levels in B cells. In addition, primary EBV infection has been shown to increase oxidative stress in B cells, epithelial cells, and lymphoblastoid cell lines (30), as well as in EBV-positive tumor cells (5,10). In contrast to our results, Gruhne et al (20) reported that EBNA1 did not affect ROS or NOX2 transcripts in epithelial cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Earlier studies have reported increased levels of ROS during primary EBV infection (26) and in EBV-carrying tumor cells (18,19), attributing this effect to virion-mediated triggering of the CR2 receptor (27), induction of IL-10 by the viral EBV-encoded, untranslated RNAs (EBERs) (18), or induction of lipoxygenases by unknown viral genes (19). Although it is possible that EBV might have evolved different strategies for inducing ROS during different phases of the infection, the selective up-regulation of NOX2 and activation of the NADPH oxidase in EBNA-1-positive B cells suggest a pivotal role of ROS in growth transformation.…”
Section: Discussionmentioning
confidence: 95%
“…Herpes simplex virus 2 (HSV-2) induced a 1.5-to 2-fold increase in ROS production 1 h after the infection of RAW 264.7 cells (64). Similarly, the gamma-1 herpesvirus Epstein-Barr virus (EBV) induced oxidative stress during the early stages of primary infections in B lymphocytes and epithelial and lymphoblastic cell lines (65). In this study, a 2-fold increase in malondialdehyde activity, indicative of lipid peroxidation, was measured.…”
Section: Discussionmentioning
confidence: 99%